Renewable energy sources as an instrument to support the competitiveness of agro-industrial enterprises and reduce their costs - Dudin, Mihail Nikolaevich; Zasko, Vadim Nikolaevich; Dontsova, Olesya Igorevna; Osokina, Irina Valentinovna; Berman, Alisa Mikhailovna (International Journal of Energy Economics and Policy, 2018)
The intensive development of the Russian agro-industrial complex is accompanied by high energy consumption, which ultimately may result in environmental pollution and ecological imbalance. The dependence of the agricultural production on organic fuels (i.e. traditional hydrocarbon energy sources) may limit the ability of this sector to meet the demand for agricultural products and ensure the food security of the country. Moreover, the high dependence of the agricultural production on traditional energy sources affects the business profitability and competitiveness. Based on the materials outlined in this article, the authors come to the following main conclusions: i) the adoption of innovative energy saving models is required for the reliable energy supply and improvement of the efficiency of agricultural production. Moreover, the damage to the environment caused by the utilization of fossil fuels can be mitigated by using renewable energy sources; ii) Russia has the climatic conditions required for the use of solar energy, small hydropower, and wind energy. At the same time, in the part of ensuring the energy needs of agro-industrial and agricultural production in Russia, traditional hydrocarbon energy sources are mainly used. Keywords: agriculture, energy supply, renewable energy, hydrocarbon energy, costs, competitiveness, food security. JEL Classifications: Q10, Q40, Q49